Métodos de inducción floral en plantas de piña (Ananas comosus) - Manzano Galarza, Andrea Gabriela (2024)
The pineapple with its scientific name ananás comosus is a fruit native to South America, pineapple is the name that it is still known in Brazil, its family is Bromeliaceae, the pineapple is a fruit composed of the union of several flowers around a fleshy axis In Ecuador, the territory with the largest pineapple plantation is the Concordia province of Santo Domingo. Regarding floral induction, it is necessary to be able to obtain maximum potential in cultivation, light, irrigation, phytohormones, gases. such as ethylene, alpha-naphthaleneacetic acid among others, also help floral induction Floral induction is the number one step for a flower to develop in the internal part, and consequently floral differentiation arrives, induction is necessary to achieve the greatest beneficial development to obtain a fruit in optimal conditions and with a satisfactory sweetness. For both export and domestic palates, floral induction has two phases, one that is reintegrated and the other that is not. Any plant that is forced to undergo floral induction must have an adequate weight and a considerable number of leaves since these conditions have a close similarity with the result of the fruits. As for the environmental conditions, they are crucial for the good development of a fruit, therefore if the temperature were to become low this would cause acid in the pineapple but if it were the opposite plus the good humidity of the soil, we would obtain a good sweet fruit. and meaty. This fruit must be harvested when it is completely ripe, otherwise it will rot. As for water, this crop is not very demanding. It stores water in the leaves that will be used later. Pineapple planting can also be done by crown, as long as it is fresh and as cared for as possible, in the world there are 6 varieties of pineapple, the smooth cayenne being the best known in the world.